The Duties and Liability of Notary as Public Official in Criminal Law Perspective - Jaya Kesuma (Magister Kenotariatan Universitas Pasundan, 2020)
A notary always leads to criminal relations in their daily profession. The Notary has to the extent their precautionary principle to prevent the malpractice practice. Mant regulations and the ethics code of the profession must have appropriate attention to protect their profession. Duties and Responsibilities of the Notary as a General Officer of the Criminal Law Perspective, which constitutes the scope of the parameters of the Notary's actions in his authority. With the hope that the Notary profession must maintain the integrity and nobleness in the future, the Notary will be a partner of law enforcement officers in providing the best legal services for the community.